Family Institution: A Study of Socio-Economic Factors of Senior Citizens to Old Age Homes in Lahore (Journal of Social Sciences Review, 2023)
The study's overarching goal was to investigate how social and economic factors influence family institutions and ultimately lead to the institutionalization of care for loved ones. Qualitative and descriptive research methods were used in this investigation. New studies show that social and economic variables affect the family unit, leading people to look for care for their golden years in institutional settings. The major demographic included seniors in institutional settings like nursing homes, retirement communities, and assisted living facilities. For this study, we used a systematic approach to identify 30 retirees from various communities in and around Lahore. In-depth interviews with an interview guide yielded the data. Interviews were conducted with key personnel who had direct responsibility for the retirees. Thematic analysis was used to draw out recurring topics once qualitative data had been collected.
Keywords: Family Institution; Socio- Economic Factors; Senior Citizens; Effects of Mobility; Substitutes of the Family